2017
DOI: 10.20944/preprints201701.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytomedicine in Joint Disorders

Abstract: Chronic joint inflammatory disorders such as osteoarthritis and rheumatoid arthritis have in common an upsurge of inflammation, and oxidative stress, resulting in progressive histological alterations and disabling symptoms. Currently used conventional medication (ranging from painkillers to biological agents) is potent, but frequently associated with serious, even life-threatening side effects. Used for millennia in traditional herbalism, medicinal plants are a promising alternative, with lower rate of adverse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 87 publications
0
35
0
1
Order By: Relevance
“…"Budburst" corresponded with the Weih definition of bud burst (stage 3) 33 and stage 10 as suggested by Saka and Kuzovkina 19 10 whereby "green tip elongates but leaves till remain in a tight cluster (>5 mm)". Tissue from multiple shoots was cut with scissors and immediately snap-frozen in liquid nitrogen at the following number of days after budburst (T): 3,4,5,6,7,8,9,10,12,15,30,45 and 60. For T3-T5 stages tissue from 2 plants (multiple stems) were pooled for each biological replicate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Budburst" corresponded with the Weih definition of bud burst (stage 3) 33 and stage 10 as suggested by Saka and Kuzovkina 19 10 whereby "green tip elongates but leaves till remain in a tight cluster (>5 mm)". Tissue from multiple shoots was cut with scissors and immediately snap-frozen in liquid nitrogen at the following number of days after budburst (T): 3,4,5,6,7,8,9,10,12,15,30,45 and 60. For T3-T5 stages tissue from 2 plants (multiple stems) were pooled for each biological replicate.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the medicinal activity of herbal extracts of willow cannot be accounted for by the levels of salicin alone 12,13 , indicating a potential for new bio-active or synergistic metabolites. Furthermore, there is now increased clinical interest in utilising willow bark extractives, particularly in the long-term treatment of arthritic pain 14,15 .…”
mentioning
confidence: 99%
“…In a recent 263 review, Shara and Stohs (2015) came to the conclusion that the anti-inflammatory activity of SA is 264 associated with down regulation of the pro-inflammatory effect of TNF-α. In addition to salicin, 265 SA has other active compounds like polyphenols and flavonoids which may also play a role in the 266 therapeutic action of SA (Dragos et al, 2017). On the other hand, HA didn't seem to have any 267 impact on the level of TNF-α in RA rats.…”
Section: Effect On Expression Of Pro-inflammatory and Cartilage Degramentioning
confidence: 99%
“…Boswellia Serrata, Curcuma longa, and Vitis vinifera showed very interesting in vitro and in vivo anti-inflammatory and antioxidant action (Di Francesco et al, 2018;Gomaa, Farghaly, El-Sers, Farrag, & Al-Zokeim, 2018;Vaughn, Branum, & Sivamani, 2016), and have been used to treat various inflammatory diseases (Algieri et al, 2015;Dey, Chaskar, Athavale, & Chitre, 2015;Dragos et al, 2017). The combination of these three plant extracts in one single supplement have never been clinically or biologically assessed in dermatological issues.…”
Section: Statistical Significance Was Measured Using Paired Data Studentmentioning
confidence: 99%